Pemanfaatan Media dan Sumber Belajar untuk Pengembangan Kognitif AUD - Fitriani, Diah Veny (Journal of Childhood Education, Development and Parenting, 2023)
The development of science and technology demands high-quality natural resources that are capable of facing various challenges. Therefore, education must always be taken into account and prioritized to produce quality individuals. Teachers, as one of the important components of successful learning, must be able to position themselves as figures who can ignite students' passion for learning. Teachers play a crucial role in the success of learning. They are not just instructors but also motivators and drivers of students' learning interest. An effective teacher should be able to ignite students' desire to learn. One way teachers can achieve this is by understanding the needs and interests of students. Teachers need to recognize the characteristics and potentials of each student so that they can adapt teaching methods and materials accordingly. Teachers also need to build positive emotional relationships with students so that students feel comfortable and motivated to learn. Additionally, teachers need to utilize various technologies and innovations in the learning process. The use of technology can help teachers present materials in a more engaging and interactive way, making students more interested and involved in learning. By leveraging technology, teachers can also bring relevant and up-to-date content into the learning environment. Moreover, teachers should serve as role models for students. They should have in-depth knowledge and continue to develop themselves in their field. Teachers with up-to-date knowledge will be able to inspire and motivate students to continue learning and self-development. In the face of rapid developments in science and technology, education must always be taken into account and prioritized. Teachers, as crucial components of successful learning, have a crucial role in igniting students' passion for learning. With quality education, it is expected to create human resources capable of facing various challenges in the era of scientific and technological advancements.